An approach to transportation network analysis via transferable utility games. (November 2017) - Hadas, Yuval; Gnecco, Giorgio; Sanguineti, Marcello
Highlights: A game-theoretic approach is used to measure centrality of nodes. The approach is based on cooperative games with transferable utility. The approach evaluates nodes based on their joint contribution to the network. Suitable utility functions are used to integrate demand within the analysis. Abstract: Network connectivity is an important aspect of any transportation network, as the role of the network is to provide a society with the ability to easily travel from point to point using various modes. A basic question in network analysis concerns how "important" each node is. An important node might, for example, greatly contribute to short connections between many pairs of nodes, handle a large amount of the traffic, generate relevant information, represent a bridge between two areas, etc. In order to quantify the relative importance of nodes, one possible approach uses the concept of centrality. A limitation of classical centrality measures is the fact that they evaluate nodes based on their individual contributions to the functioning of the network. The present paper introduces a game theory approach, based on cooperative games with transferable utility. Given a transportation network, a game is defined taking into account the network topology, the weights associated with the arcs, and the demand based on an origin-destination matrix (weights associated with nodes). The network nodes represent the players in such a game. The Shapley value, which measures the relative importance of the players in transferable utility games, is used to identify the nodes that have a major role. For several network topologies, a comparison is made with well-known centrality measures. The results show that the suggested centrality measures outperform the classical ones, and provide an innovative approach for transportation network analysis.